Prevalence estimates of ADHD in a sample of inpatients with alcohol dependence - Luderer, Mathias; Sick, Christian; Kaplan-Wickel, Nurcihan; Reinhard, Iris; Richter, Agnes; Kiefer, Falk; Weber, Tillmann (Sage, 2020)
Objective: ADHD is common in patients with alcohol dependence, but prevalence results are inconsistent. We investigated ADHD prevalence in a complex design to avoid over- or underdiagnosing. Method: Patients with alcohol dependence starting long-term residential treatment were included. A structured interview (Diagnostic Interview for ADHD in Adults [DIVA]) was conducted on all patients. DIVA results indicating childhood or adulthood ADHD were assessed in successive diagnostic interviews by two expert clinicians. Results: 415 of 488 patients had completed the entire diagnostic assessment. ADHD prevalence was 20.5%. DIVA results correlated moderately with experts’ diagnoses. In patients with ADHD, a higher comorbid illicit substance use was prevalent and alcohol dependence started earlier and was more severe. Conclusion: This study provides the largest sample on ADHD prevalence in alcohol dependent inpatients. Despite great efforts to avoid overestimation, we found every fifth patient to have ADHD. ADHD diagnosis should not be based solely on a structured interview but should be clinically confirmed. (J. of Att. Dis. 2020; 24(14) 2072–2083).